SCREENING FOR MEDULLARY CARCINOMA IN PEOPLE WITH THYROID NODULES - Jandrić-Kočić, Marijana (HEALTH CARE, 2024)
Background/Aim: Medullary thyroid cancer (MTC) is a rare neuroendocrine neoplasm, which arises from parafollicular C cells, which secrete calcitonin. Calcitonin is a sensitive tumor marker of MTC, bearing in mind that the majority of patients have elevated values ​​of it. However, there is no consensus on the use of calcitonin as a screening test for the early detection of MTC in individuals with thyroid nodules. The aim of the research was to analyze the possibility of introducing calcitonin as a screening test for the early detection of MTC through a case report. Case report: The paper presents a 56-year-old female patient who, during a systematic examination, was found to have nodules with a diameter of 10 x 8 mm and 5 x 4 mm in the right lobe of the thyroid gland. Laboratory analysis revealed slightly elevated calcitonin values ​​(7.8 pg/mL, reference values ​​< 4.8 pg/mL). The calcium stimulation test was within the reference range, and the carcino-embryonic antigen values ​​were normal. Cytological examination of fine-needle aspiration puncture samples corresponded to category T2 according to the Bethesda classification (Chronic lymphocytic thyroiditis of the Hashimoto type). At the control examination, carried out after 6 months, calcitonin values ​​did not differ significantly compared to the original ones. Conclusion: In the presented patient, the discreetly elevated concentration of calcitonin in the serum did not imply the presence of MTC. Further randomized clinical trials are needed to resolve controversies and establish uniform guidelines for the introduction of calcitonin as a screening test for MTC in individuals with thyroid nodules.